Plasma protein markers for estimating the population genetic structure of Amazon turtle (Podocnemis expansa Schweigger, 1812) - AS, Teixeira; AS, Moura (Journal of Research in Biology, 2012)
This study aims to test the potential of allelic frequency distributions of plasma proteins analysed by starch gel electrophoresis for identifying Amazon turtle (Podocnemis expansa Schweigger, 1812) stocks. Three proteins: transferrin (Tf), albumin (Alb) and general protein (GP), and four enzymes: esterase (EST), phosphoglucomutase (PGM), malate dehydrogenase (MDH) and superoxide dismutase (SOD) from three geographical areas in the Amazon region, totalizing three population samples: 1) Maracarana, Rio Uatumã-AM, 2) Trombetas, Rio Trombetas-PA and 3) Monte Cristo, Rio Tapajós-PA, were tested. Out of 11 presumptive loci detected, seven were monomorphic (GP-1, GP-2, EST-1, EST-2, PGM-1, SOD-1 and SOD-2) and four polymorphic (Tf, Alb, MDH and PGM-2). The chi-square (X2) analysis for testing the hypothesis of independent segregation between pairs of polymorphic loci in the population samples, revealed no statistically significant differences. Based on Wright’s F-statistics (FIS, FIT and FST) the detected average value of FIS = 0.1347, indicates a moderate inbreeding within the population samples, whereas the average value of FIT = 0.1912, indicates a moderately great inbreeding in the total population sample.The detected average value of FST = 0.0652, indicates a moderate genetic differentiation among the population samples. The pairwise comparisons of FST point to a moderate differentiation between all comparisons made with the Monte Cristo population sample (FST ranging from 0.061 to 0.066); but very little differentiation was detected between Maracarana and Trombetas samples (FST = 0.0035). A limited gene flow among the population samples was detected (Nm = 3.58). The UPGMA dendrogram showed the lowest genetic distance between population samples of Maracarana and Trombetas, whereas, the highest genetic distances were detected when these two samples were compared to that of Monte Cristo. Exact test for population differentiation revealed high levels of statistically significant differences in all pairwise comparisons made with the Monte Cristo sample. The data point out a possible existence of distinct subpopulations “stocks” of P. expansa in the sampled area, where Monte Cristo sample was always genetically different compared to the other two population samples examined.